Analysis of Kicks Using the Instep of the Foot against the Accuracy of Shooting into the Goal in the Game of Football - Zainuddin, Muhammad Said (Perkumpulan Dosen Muda Bengkulu, 2023)
This study aims to determine the results of kicks using the back of the foot on the accuracy of shooting in a soccer game on the Bulukumba Porprov football team. This research is a type of quantitative research. The population and sample are football players on the porprov team of Bulukumba Regency as many as 20. The test instrument used is the shooting technique at the goal. The data analysis technique used was descriptive analysis using the SPSS Version 22.00 program. The conclusion from the results of the data obtained is the result of a kick using the back of the foot on the accuracy of shooting in a soccer game on the Bulukumba Porprov football team. are in the less category with a percentage of (30%).